The Organizational Profile of SMEs (Micro, Small, and Medium Enterprises) in the Manufacturing Sector: A Comprehensive Analysis - Cabello Chávez, Adalberto; Reyes Avellaneda, Rafael; Solís Pérez, Pedro (Administración y Organizaciones, 2025)
The SMEs (micro, smalls and mediums enterprises) in the manufacture sector are represented by differences organization configuration: the organization as open system, the organization as auto regulate system with entrance and departure, the organization as a representation of the two systems: the formal and the social, the organization seeing for enterprise organization. The representation of the SMEs lets identification as familiar’s enterprises, with financial save, with concentrate the most economics resources in the premium matter, and the orientation is a locals o concentrates niches. Wherever the SMEs are in formals organizations, that tendency is the disorder in hers functioned, in the direction there is a triple role of the entrepreneur, of: family member, proprietary, and director, in the operation a double role of: family member and worker. For all the characteristics found in the SMEs by Organization Theory, is more adequate identifies as a SMOs (micro, smalls and mediums organizations).